Analysis of Cigarette Law According to Muhammadiyah Figures in Aceh Tamiang - Muhammad (Tunas Institute, 2023)
Smoking is an activity that has become part of the culture and habits of society, especially in Indonesia. There is no one who doesn't know cigarettes, whether they are smokers or those who don't smoke. If so, from an Islamic perspective, smoking is a new study because smoking or smoking laws were not formulated with certainty in Nash during the time of the Prophet Muhammad SAW. So cigarette law is a new study in the study of Islamic law. In Indonesia, in particular, there are several smoking laws, from those that are forbidden to those that are forbidden, where these smoking laws are divided into several fatwas, both issued by official state institutions and by certain institutions or organizations such as Muhammadiyah. According to Muhammadiyah itself, the law on cigarettes is haram. This is based on several rules and understanding of the Koran and hadith which were stated in the Muhammadiyah fatwa and was issued in 2010. There are several methods used by Muhammadiyah in giving fatwas related to smoking law, which in the big picture divided into 3 models of ijtihad, namely Ijtihad Bayani, ijhtihad Qiyasi and Ijtihat Ishtilahi. Apart from using the ijtihad method, Muhammadiyah also uses the understanding contained in Maqashid Syariah or the goal of search by focusing on the preservation of soul, property, mind, soul and body. However, apart from the cigarette law, we as humans should not make cigarette law cases into cases that are used to divide people because smoking is a very branch thing and not a main legal discussion such as discussing the angle in jinayah.